Design of a microstrip patch antenna for the Ku band applications. (2021) - Islam, Mohammad Tawsiful; Mahmud, Md. Sultan; Islam, Md. Hobaibul; Shahriar, Al; Islam, Sikder Sunbeam; Faruque, Mohammad Rashed Iqbal; Gulib, Asadulla Hil
Abstract: This paper presents a new high gain and highly efficient Microstrip Patch Antenna for Ku band application. The proposed antenna uses a copper (annealed) patch imposed over the FR-4 substrate. The constructed design offers Return loss = −26.5578 dB, Gain = 6.31 dBi at resonant frequency 12.54 GHz, Voltage Standing Wave Ratio = 1.0986392, Bandwidth = 4.1553 GHz (33.14%) and Efficiency = 98.99%, all results are shown in simulation results. This proposed antenna is aimed to increase the capability for Ku band application also employed for wireless application. Computer Simulation Technology software (CST) has been used to execute this design, simulation, and perform analysis. The simulated results represent that this patch antenna achieves better performance in terms of gain, directivity, and return loss.